math
 👍 0
 👎 0
 👁 1,857

 👍 1
 👎 1
👩🏫Ms. Sue 
 👍 4
 👎 2

 👍 0
 👎 2

 👍 0
 👎 1

 👍 0
 👎 1
Respond to this Question
Similar Questions

math
a)simplify the expression and explain each step 4(3x+2)2 b)Factor the expression below 20b16 help please

math
math a)simplify the expression and explain each step 4(3x+2)2 b)Factor the expression below 20b16 help please

math
Consider the sequence of steps to solve the equation: 5(x  3) = 7x 2 Step 1 ⇒ 10(x  3) = 7x Step 2 ⇒ 10x  30 = 7x Step 3 ⇒ 3x  30 = 0 Step 4 ⇒ 3x = 30 Step 5 ⇒ x = 10 Identify the property of equality which yields

mathematics
Note: Enter your answer and show all the steps that you use to solve this problem in the space provided. a)Simplify the expression and explain each step 4(3x+2)2 b)Factor the expression below 20b16

Math
Note: Enter your answer and show all the steps that you use to solve this problem in the space provided. a) Simplify the expression and explain each step. (2 points) 12 + 3 ( 2 y − 3 ) 12+3(2y  3) b) Factor the expression

Math
a) Simplify the expression and explain each step. 4(3x + 2)  2 b) Factor the expression completely. 20b  16 I'm not asking for answers. I just want help figuring out what the letters in the equation mean. Thanks!

math
Consider the sequence of steps to solve the equation: 2(x − 4) + 6x = 9x − 10 Which step in solving this equation is justified by the Commutative Property of Addition? Given ⇒ 2(x − 4) + 6x = 9x − 10 Step 1 ⇒ 2x − 8

ALGEBRA HELP
When solving the equation, what property was used to go from step 3 to step 4? Step 1: (2x+3= x18 Step 2: 2x3=x18 Step 3: 3=3x18 Step 4: 15=3x A)APOE B)SPOE C)MPOE D)DPOE

math
(3.2b+0.8)+1.9b simplify the expression.explain each step

math
Algebra 1.) Use the distributive Property to simplify the expression . (1)(4  c) A. 4  c B. 4 + c C. 4 + c D.4  c 2.)Use the distributive Property to simplify the expression 4(2x  4) A.8x + 4 B.8x  4 C.8x  16 D.4x  16

math
An equation and the steps to solve it are shown below: 3x − one over two (8x − 2) = 4 Step 1: 3x − 4x + 1 = 4 Step 2: x + 1 = 4 Step 3: x + 1 − 1 = 4 − 1 Step 4: x = 3 Which step was the error made and why? Step 1,

Help PLZ!!
consider the steps to simplify the expression. Which property is used to reach Step 3? Expression: 4 3 7 + 7 + (3 4 7 ) Step 1: = 4 3 7 + (3 4 7 ) + 7 Step 2: = 4 + ( 3 7 ) + (3) + ( 4 7 ) + 7 Step 3: = 4 + ( 3 7 ) + (
You can view more similar questions or ask a new question.